The contribution of major mergers to the creation of spheroidal galaxies and the build up of stellar mass at z≃2. Issue Volume 11:Issue S319(2015) (17th August 2016) - Lofthouse, E. K.; Kaviraj, S.; Conselice, C. J.; Mortlock, A.
Abstract: We investigate the contribution of major mergers to star formation in spheroidal galaxies at z 2. Galaxies are visually classified from a sample of massive galaxies in CANDELS. At the redshifts used, the observed morphological disturbances are due to recent major mergers as minor mergers are too faint. The percentage of blue spheroids showing morphological disturbances is 21 ± 4%, indicating that major mergers are not the dominant star formation mechanism in these galaxies. Thus, minor mergers or cold accretion are likely to be the main drivers of star formation. We investigate the U-band luminosity emission of the sample and find that only a small fraction of the cosmic L(U) is from galaxies involved in a major merger, 30%. Using the ratio of specific star formation rate for LTGs to mergers and combining this with the results for the luminosity budget shows that only 6% of the total L(U) emitted at z 2 is due to the major merger process.